Knowledge and Attitudes of Forest Officers Towards Forestry Law and its Enforcement in LAO PDR - Vongsiharath, Vongdeuane (2001)
The study was conducted in three provinces of Lao PDR; namely, Louangprabang, Kbammouane and Champasack with the main objective of assessing the knowledge and attitudes of forest officers towards the Forestry Law of 1996 in Lao PDR, as well as the factors affecting knowledge and attitudes. The data for the study were gathered from 264 respondents through a self-administered questionnaire survey. The respondents were requested to indicate their responses in a three-point scale to twenty four statements on knowledge of Forestry Law 1996 and in a five-point scale on attitude statements about forestry law and its enforcement. The scores obtained through these responses measured the knowledge and attitudes of the respondents. Frequency and correlation analyses were done on the data employing appropriate statistical techniques. Overall, knowledge of the forest officers of forestry law in Lao PDR was poor. This could be attributed to the law being new, familiarity with the previous laws, lack of law enforcement experience as well as length of service. However, they have good knowledge on provision related to forest conservation aspect. Four independent variables were found to have significant and positive correlation with the respondents' knowledge, namely; academic qualification, place of work, training attendance and meeting attendance. On the other hand, the respondents have positive attitudes towards the forestry law enforcement system and the co-operation rendered organisations in enforcing the law. However, they expressed dissatisfaction towards the government support for enforcing the law. Five variables were found to have correlation with the respondents' attitudes. Three of these, namely; academic qualification, current position, and meeting attendance were positive, while length of services and place of work were negatively correlated. Generally, there was no relationship between the respondents' knowledge and attitudes. However, there was significant correlation between knowledge and attitudes of some sub-groups of those who were trained on forestry, served a longer period of time, worked in district, and have attended the training and meetings.